Biased Expectations and Labor Market Outcomes: Evidence from German Survey Data and Implications for the East-West Wage Gap - Almut Balleer; Georg Duernecker; Susanne Forstner; Johannes Goensch (Center for Economic Studies and ifo Institute (CESifo), 2023)
We measure individual bias in labor market expectations in German survey data and find that workers on average significantly overestimate their individual probabilities to separate from their job when employed as well to find a job when unemployed. These biases vary significantly between population groups. Most notably, East Germans are significantly more pessimistic than West Germans. We find a significantly negative relationship between the pessimistic bias in job separation expectations and wages, and a significantly positive relationship between optimistic bias in job finding expectations and reservation incomes. We interpret and quantify the effects of (such) expectation biases on the labor market equilibrium in a search and matching model of the labor market. Removing the biases could substantially increase wages and expected lifetime income in East Germany. The bias difference in labor market expectations explains part of the East-West German wage gap.
Keywords: E24; J31; D84; 330; labor market risk; biased beliefs; wages; reservation wages